Mood‐stabilizers differentially affect housekeeping gene expression in human cells. Issue 2 (12th February 2014) - Powell, Timothy R.; Powell‐Smith, Georgia; Haddley, Kate; Mcguffin, Peter; Quinn, John; Schalkwyk, Leonard C.; Farmer, Anne E.; D'Souza, Ursula M.
Abstract Recent studies have revealed that antidepressants affect the expression of constitutively expressed "housekeeping genes" commonly used as normalizing reference genes in quantitative polymerase chain reaction (qPCR) experiments. There has yet to be an investigation however on the effects of mood‐stabilizers on housekeeping gene stability. The current study utilized lymphoblastoid cell lines (LCLs) derived from patients with mood disorders to investigate the effects of a range of doses of lithium (0, 1, 2 and 5 mM) and sodium valproate (0, 0.06, 0.03 and 0.6 mM) on the stability of 12 housekeeping genes. RNA was extracted from LCLs and qPCR was used to generate cycle threshold (Ct) values which were input into RefFinder analyses. The study revealed drug‐specific effects on housekeeping gene stability. The most stable housekeeping genes in LCLs treated: acutely with sodium valproate were ACTB and RPL13A; acutely with lithium were GAPDH and ATP5B; chronically with lithium were ATP5B and CYC1. The stability of GAPDH and B2M were particularly affected by duration of lithium treatment. The study adds to a growing literature that the selection of appropriate housekeeping genes is important for the accurate normalization of target gene expression in experiments investigating the molecular effects of mood disorder pharmacotherapies. Copyright © 2014 John Wiley & Sons, Ltd.